Seaweeds as Preventive Agents for Cardiovascular Diseases: From Nutrients to Functional Foods - Cardoso, Susana M. (Mar Drugs, 2015)
Being naturally enriched in key nutrients and in various health-promoting compounds, seaweeds represent promising candidates for the design of functional foods. Soluble dietary fibers, peptides, phlorotannins, lipids and minerals are macroalgae’s major compounds that can hold potential in high-value food products derived from macroalgae, including those directed to the cardiovascular-health promotion. This manuscript revises available reported data focusing the role of diet supplementation of macroalgae, or extracts enriched in bioactive compounds from macroalgae origin, in targeting modifiable markers of cardiovascular diseases (CVDs), like dyslipidemia, oxidative stress, vascular inflammation, hypertension, hypercoagulability and activation of the sympathetic and renin-angiotensin systems, among others. At last, the review also describes several products that have been formulated with the use of whole macroalgae or extracts, along with their claimed cardiovascular-associated benefits.